Dissent in the sediment? Lake sediments as archives of short- and long-range impact of anthropogenic activities in northeastern Germany - Simon, Marcel Pierre; Schatz, Marlene; Böhm, Leonard; Papp, István; Grossart, Hans-Peter; Andersen, Thorbjørn Joest; Bálint, Miklós; Düring, Rolf-Alexander; Justus Liebig University Giessen (My University, 2023)
The suitability of lake sediment cores to reconstruct past inputs, regional pollution, and usage patterns of pesticides has been shown previously. Until now, no such data exist for lakes in eastern Germany. Therefore, 10 sediment cores (length 1 m) of 10 lakes in eastern Germany, the territory of the former German Democratic Republic (GDR), were collected and cut into 5–10-mm layers. In each layer, concentrations of trace elements (TEs) As, Cd, Cr, Cu, Ni, Pb, S, and Zn, as well as of organochlorine pesticides (OCPs), i.e., dichlorodiphenyltrichloroethane (DDT) and hexachlorocyclohexane (HCH), were analyzed. A miniaturized solid–liquid extraction technique in conjunction with headspace solid-phase microextraction (HS-SPME) and gas chromatography–mass spectrometry (GC–MS) was used for the latter. The progression of TE concentrations over time is uniform. It follows a trans-regional pattern and is indicative of activity and policy making in West Germany before 1990 instead of those in the GDR. Of OCPs, only transformation products of DDT were found. Congener ratios indicate a mainly aerial input. In the lakes’ profiles, several regional features and responses to national policies and measures are visible. Dichlorodiphenyldichloroethane (DDD) concentrations reflect the history of DDT use in the GDR. Lake sediments proved to be suitable to archive short- and long-range impacts of anthropogenic activity. Our data can be used to complement and validate other forms of environmental pollution long-term monitoring and to check for the efficiency of pollution countermeasures in the past.
Keywords: ddc:630